CRISIS IN ENTERPRISE – THE ESSENCE AND NECESSITY OF MANAGEMENT - KUPALOVA, HALINA; GONCHARENKO, NATALIIA; KORENEVA, NATALYA; MALINOVSKA, DARIA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers the theoretical prerequisites for crisis management in business. The relevance this problem studying is outlined by the crisis manifestation permanence during all the years of Ukraine independence. Having analyzed the processes of emergence and passage of the crisis, their appearance was identified not because of socio-economic changes in society (they always humanity accompany), but because of inability to detect, control and respond to imbalances in the enterprise management system. Often, the "crisis" is a "turning point", "negative process", "exacerbation of contradictions in the system", "evolutionary process of enterprise development", "stage of the enterprise life cycle", "potential for change", "random factor". It should be emphasized that to describe the crisis of the enterprise are often used as equal concepts "crisis phenomenon", "crisis situation", "crisis situation", "crisis". However, they all differ in time and consequences for the system. When forming anti-crisis policy in the enterprise, any problem in any business process, which is left without attention and analysis now, in the future has every chance to turn into a crisis. Crises in the company are different in nature, causes and consequences. Therefore, the success of crisis management depends on the timely recognition of symptoms. Understanding the causes of the crisis (disease) will help to invent a "cure" - counter-shock or anti-crisis measures. There should be a specific list of anti-crisis actions for each type of crisis and its stage. Therefore, in our opinion, crisis management is a set of timely point management measures to diagnose, neutralize, prevent and overcome crises at a particular stage of the crisis in the subordinate system in conditions of risk and uncertainty.
Keywords: crisis; crisis phenomena; crisis situation; crisis state; anti-crisis management